Autonomic Dysfunction in Autism Spectrum Disorder - Owens, Andrew P.; Mathias, Christopher J.; Iodice, Valeria (Frontiers in Integrative Neuroscience, 2021)
Background: There have been previous reports of enhanced sympathoexcitation in autism spectrum disorder (ASD). However, there has been no formal investigation of autonomic dysfunction in ASD. Also, the joint hypermobile form of Ehlers-Danlos syndrome (hE-DS) that maybe overrepresented in ASD and orthostatic related autonomic dysfunction. This study examined the comorbidity of ASD, autonomic dysfunction and hE-DS in two UK autonomic national referral centers. Proven, documented and globally accepted clinical autonomic investigations were used to assess neuro-cardiovascular autonomic function in a cohort of ASD subjects and in age-matched healthy controls. Methods: Clinical data from 28 referrals with a confirmed diagnosis of ASD over a 10-year period were compared with 19 age-matched healthy controls. Autonomic function was determined using methods established in the centers previously described in detail. Results: 20/28 ASD had a diagnosed autonomic condition; 9 had the postural tachycardia syndrome (PoTS), 4 PoTS and vasovagal syncope (VVS), 3 experienced presyncope, 1 essential hyperhidrosis, 1 orthostatic hypotension, 1 VVS alone and 1 a combination of PoTS, VVS and essential hyperhidrosis. 16/20 ASD with autonomic dysfunction had hE-DS. In ASD, basal heart rate and responses to orthostatic tests of autonomic function were elevated, supporting previous findings of increased sympathoexcitation. However, sympathetic vasoconstriction was impaired in ASD. Conclusion: Intermittent neuro-cardiovascular autonomic dysfunction affecting heart rate and blood pressure was over-represented in ASD. There is a strong association with hE-DS. Autonomic dysfunction may further impair quality of life in ASD, particularly in those unable to adequately express their experience of autonomic symptoms.